Sulphur and Nitrogen Fertilization as a Potential Means of Agronomic Biofortification to Improve the Content and Uptake of Microelements in Spring Wheat Grain DM - Hanna Klikocka; Marek Marks (Journal of Chemistry)
The aim of the field experiment was to analyze the impact of various nitrogen and sulphur doses on the content and uptake of spring grains of iron, manganese, copper, and zinc. The study was conducted in southeastern Poland (2009–2011) on Cambisols (WRB 2007), in conditions of low soil sulphur content. The experiment included 4 doses of N fertilization (0, 40, 80, and 120 kg/ha) and 2 doses of S application (0 and 50 kg/ha). The analysis showed that fertilization with nitrogen and sulphur had a positive effect on the studied features of spring wheat. The combination resulted in beneficial content of Fe, Mn, Zn, and Cu (Fe 45.00, Mn 35.67, Zn 34.63, and Cu 3.65 mg/kg) and beneficial uptake of microelements by grain DM (Fe 216.1, Mn 171.3, Zn 166.4, and Cu 17.52 g/ha). The highest grain yield (5.43 t/ha) was obtained after the application of nitrogen at a dose of 80 kg/ha and sulphur at a dose of 50 kg/ha. In relation to control, this increase of grain yield amounted to 13.3%. Significant correlations were also found between grain yield and the content and uptake of all microelements, as well as between elements. No significant correlation was found only between the content and uptake of Fe and the content of Mn and between the content of Mn and Cu. Sulphur supplementation of NPK fertilization can be a good means of agronomic biofortification for spring wheat in order to increase the content and uptake of micronutrients such as Fe, Mn, Zn, and Cu.